2021
DOI: 10.1155/2021/1837729
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial Antibacterial Technology in the Design of Antibacterial Fabrics for Sports Clothing

Abstract: In recent years, nanomaterials have been widely used in sports equipment, and their application in sportswear has also attracted wide attention. This research mainly discusses the application of nanomaterial antibacterial technology in the design of antibacterial fabrics for sports apparel. The method of adding nano-TiO2 to the antibacterial textiles varies with the type of fiber or fabric, and the finishing method also changes accordingly. For chemical fibers, the method of blending spinning is mainly used. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…They are also employed in sportswear fashion and in the military sector to prevent bacterial proliferation and infections and for odor control. 10,11 It has been demonstrated that microorganisms can be transferred from contaminated textiles to surfaces, where they can persist for months, forming biofilms and leading to bacteria transmission. 12−14 Antimicrobial effects in textiles can be achieved through the incorporation of a biocide molecule in the coating mixture applied during the finishing stage, by immersion in a solution containing the active antibacterial principle, also called "in foulard" treatment, 15 or through the incorporation into fibers during the spinning process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are also employed in sportswear fashion and in the military sector to prevent bacterial proliferation and infections and for odor control. 10,11 It has been demonstrated that microorganisms can be transferred from contaminated textiles to surfaces, where they can persist for months, forming biofilms and leading to bacteria transmission. 12−14 Antimicrobial effects in textiles can be achieved through the incorporation of a biocide molecule in the coating mixture applied during the finishing stage, by immersion in a solution containing the active antibacterial principle, also called "in foulard" treatment, 15 or through the incorporation into fibers during the spinning process.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial textiles nowadays are often used in hygienically demanding areas such as the food sector, hospitals, or nursing homes to improve the environmental hygiene and prevent nosocomial infections. They are also employed in sportswear fashion and in the military sector to prevent bacterial proliferation and infections and for odor control. , It has been demonstrated that microorganisms can be transferred from contaminated textiles to surfaces, where they can persist for months, forming biofilms and leading to bacteria transmission. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial fabrics are also used as hospital bed sheets, curtains, and patient clothing, etc., to reduce cross-infection [7]. Outside of hospital settings, antimicrobial textiles are being used in regular clothes [8] and sportswear [9].…”
Section: Introductionmentioning
confidence: 99%